Chemokines in allergic asthma inflammation - Sulfiana Sulfiana; Febriana Catur Iswanti (Universa Medicina, 2022)
Asthma is the most frequent noncommunicable disease and one of the leading causes of years lived with disability. Asthma has a severe impact on a patient's life, being able to disturb the activities of both children and adults. The morbidity and mortality of asthma may depend on the severity and progressiveness of the symptoms experienced by the patient. Different and complex pathomechanisms underline the pathology of asthma, in which the regulation of innate and adaptive immune responses plays a role. There is a complex interaction between immune cells including chemokines involved in the pathogenesis of asthma. Immune cell trafficking is orchestrated by a family of small proteins called chemokines. Leukocytes express cell-surface receptors that bind to chemokines and trigger transendothelial migration. This review article outlines the main role of chemokines in inflammatory reactions that occur in allergic asthma, based on the latest literature studies that have been published previously. The allergic reaction in asthma expresses various chemokines and their receptors. Chemokines including eotaxins (CCL11, CCL24, and CCL26), CCL2, CCL5, CCL17, and CCL22 regulate immune cells that under pathological conditions travel to the inflammatory site, mainly in the lung, to protect the body from pathogen invasion. Chemokines are released by a number of immune cells such as monocytes, dendritic cells, mast cells, and epithelial cells in the airway. The biological effects of chemokine production are enhanced by secreted cytokines when an allergic reaction occurs in asthma, such as IL-4, IL-5, and IL-13. Chemokines cause an accumulation of different inflammatory cells at the site of inflammation, which ultimately results in tissue damage to the airway. The inhibition of the reactions evoked by the interaction between chemokines and their receptors is considered a candidate for the development of potent therapeutic drugs for asthma in the future.